LIN28B overexpression defines a novel fetal-like subgroup of juvenile myelomonocytic leukemia - Helsmoortel, Hetty H; Bresolin, Silvia; Lammens, Tim; Cavé, Hélène; Noellke, Peter; Caye, Aurélie; Ghazavi, Farzaneh; de Vries, Andrica; Hasle, Henrik; Labarque, Veerle; Masetti, Riccardo; Stary, Jan; et al. (Blood, 2016)
Juvenile myelomonocytic leukemia (JMML) is a rare and aggressive stem cell disease of early childhood. RAS activation constitutes the core component of oncogenic signaling. In addition, leukemic blasts in one-fourth of JMML patients present with monosomy 7, and more than half of patients show elevated age-adjusted fetal hemoglobin (HbF) levels. Hematopoietic stem cell transplantation is the current standard of care and results in an event-free survival rate of 50% to 60%, indicating that novel molecular-driven therapeutic options are urgently needed. Using gene expression profiling in a series of 82 patient samples, we aimed at understanding the molecular biology behind JMML and identified a previously unrecognized molecular subgroup characterized by high LIN28B expression. LIN28B overexpression was significantly correlated with higher HbF levels, whereas patients with monosomy 7 seldom showed enhanced LIN28B expression. This finding gives a biological explanation of why patients with monosomy 7 are rarely diagnosed with high age-adjusted HbF levels. In addition, this new fetal-like JMML subgroup presented with reduced levels of most members of the let-7 microRNA family and showed characteristic overexpression of genes involved in fetal hematopoiesis and stem cell self-renewal. Lastly, high LIN28B expression was associated with poor clinical outcome in our JMML patient series but was not independent from other prognostic factors such as age and age-adjusted HbF levels. In conclusion, we identified elevated LIN28B expression as a hallmark of a novel fetal-like subgroup in JMML.
Keywords: proteiny vázající RNA; transplantace hematopoetických kmenových buněk; Humans; Chromosomes, Human, Pair 7; dítě; Multivariate Analysis; Biomarkers, Tumor; Child; Hematopoietic Stem Cell Transplantation; Female; lidé; juvenilní myelomonocytární leukemie; přežití bez známek nemoci; Fetal Hemoglobin; Leukemia, Myelomonocytic, Juvenile; nádorové biomarkery; předškolní dítě; Fetus; plod; ženské pohlaví; multivariační analýza; Male; chromozomální delece; Chromosome Deletion; prognóza; regulace genové exprese u leukemie; Disease-Free Survival; fetální hemoglobin; mužské pohlaví; RNA-Binding Proteins; Child, Preschool; Prognosis; lidské chromozomy, pár 7; Gene Expression Regulation, Leukemic